The Mexican roots of the Indian lavander tree - Becerra, Judith X.; Noge, Koji (Instituto de Ecología, A.C., 2010)
The tree known as Indian lavender (Bursera delpechiana, Burseraceae) is a source of linalool. It was introduced to India from Mexico at the beginning of the 20th century for the exploitation of its essential oil. Its origin from Mexico was not well understood because the name B. delpechiana has been taxonomically obsolete for many years. We used molecular, phylogenetic, and chemical data to determine which currently recognized species it belongs to. This evidence regarding the Indian Lavender Tree’s identity all points to the Mexican species, Bursera linanoe. Our chemical analysis also revealed that linalyl acetate is the primary constituent of Indian Lavender oil as well as of Mexican B. linanoe rather than linalool as previously believed.